Liquidity risk, credit risk and the overnight interest rate spread: A stochastic volatility modelling approach - John Beirne; Guglielmo Maria Caporale; Nicola Spagnolo (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this paper we model the volatility of the spread between the overnight interest rate and the central bank policy rate (the policy spread) for the euro area and the UK during the two main phases of the financial crisis that began in late 2007. During the crisis, the policy spread exhibited signs of volatility, owing to the breakdown in interbank market activity. The determinants of this volatility are assessed using Stochastic Volatility models to gauge the role played by liquidity risk, credit risk (financial and sovereign), and interest rate expectations. Our results suggest that liquidity risk is the main determinant of the volatility of the policy spread, but also that private bank credit risk has become more apparent in the post-Lehman collapse phase of the crisis for the euro area as financial CDS premia rose due to possible default fears. In addition, the ECB appears to have been more effective in addressing liquidity risk since the onset of the crisis, and this may be related to its greater direct access to a broader range of counterparties and its acceptance of a broader range of eligible collateral. The main implication is that, in crisis times, a sufficiently flexible operational framework for monetary policy implementation produces the most timely response to market tensions.
Keywords: C32; E52; E58; 330; Overnight Interest Rate Spread; Liquidity Risk; Credit Risk; Stochastic Volatility